Denaturalising the discourse of competition in the graduate job market and the notion of employability: a corpus-based study of UK university websites. Issue 3 (26th May 2020) - Fotiadou, Maria
ABSTRACT: This paper focuses on the representation of the notion of employability and the job-seeking 'reality'. It is part of a wider research project that looks closely into the careers services sector within Higher Education Institutions in the United Kingdom. The chosen methodology, that is corpus-based critical discourse analysis, combined qualitative and quantitative methods and tools for the analysis of 2.6 million words deriving from 58 university websites, and more specifically the careers services sections. The analysis brings to light some problematic, common-sense ideas that are being disseminated by these services and encourages the denaturalisation of the careers services' discourse. It shows that the language used by careers services reproduces and promotes neoliberal ideology. In addition, it argues that the notion of employability could be interpreted as a pseudo-solution to the social problem of (youth) unemployment and fierce competition in the graduate job market .